Influence of surface activated carbon nano fiber on thermo-mechanical properties of high performance polymeric nano composites. (April 2017) - Ajeesh, G; Bhowmik, Shantanu; Sivakumar, Venugopal; Varshney, Lalit; Kumar, Virendra; Abraham, Mathew
This investigation highlights the influence of plasma modified carbon nano fiber (CNF) on the various properties of poly ether ketone (PEK). CNFs were modified with oxygen plasma under low pressure to enhance the interfacial adhesion between the reinforcement and matrix. Significant changes are evident in the elemental composition of oxygen and carbon on the plasma modified CNFs as observed by X-ray photo electron spectroscopy. Based on results from compression and tensile strength, significant change in the mechanical properties of the composites is observed. Dynamic mechanical thermal analysis (DMTA) reveals that the storage modulus increases on reinforcing modified CNF in PEK. The increase in modulus is noticeable only up to 1.5% wt reinforcement of CNF, while higher percentage of reinforcement leads to decline in properties. DMTA studies also clearly shows that the dispersion of CNF is not uniform after 1.5% of CNF reinforcement. However, differential scanning calorimeter and thermo gravimetric analysis studies reveal that the thermal properties of the CNF reinforced composite do not vary significantly. Thermal conductivity results show a substantial increase in the thermal conductivity of polymeric composites on increasing the reinforcements. Transmission electron microscopy (TEM) analysis reveals that there is uniform dispersion of CNF in PEK. TEM also clearly shows that higher percentage of CNF leads to agglomeration. Physico-chemical analysis indicates that the contact angle increases on increasing the reinforcements. These findings would be highly useful to make way for PEK composites for high temperature and high strength application.